2023
DOI: 10.18393/ejss.1181205
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal fluctuations in phthalates’ contamination in pond water: A case study

Abstract: Phthalates are endocrine disruptors, reported to cause deformities and reproductive damages in animals. Numerous studies reported the presence of phthalates in water samples of rivers, wetlands, and estuaries, while the scenario in case of ponds is different, however they are reported as an integral part of biosphere. In this study, the level of phthalates’ contamination in the water samples collected from the different ponds of Amritsar district for four consecutive seasons in two years was analysed. The maxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 81 publications
(81 reference statements)
0
1
0
Order By: Relevance
“…However, PAEs are not chemically bound to the plastic matrix [6,7], making them susceptible to detachment from plastic products and dispersion into the surrounding environment. A 2023 study revealed seasonal fluctuations in PAE concentrations within ponds across diverse regions in India, attributing these variations to seasonal changes in temperature and precipitation [8]. Moreover, research identified substantial PAEs pollution in the waters of the Persian Gulf in Iran, significantly impacting the ecological environment of the coral reefs in the area [9].…”
Section: Introductionmentioning
confidence: 99%
“…However, PAEs are not chemically bound to the plastic matrix [6,7], making them susceptible to detachment from plastic products and dispersion into the surrounding environment. A 2023 study revealed seasonal fluctuations in PAE concentrations within ponds across diverse regions in India, attributing these variations to seasonal changes in temperature and precipitation [8]. Moreover, research identified substantial PAEs pollution in the waters of the Persian Gulf in Iran, significantly impacting the ecological environment of the coral reefs in the area [9].…”
Section: Introductionmentioning
confidence: 99%